Arsenic trioxide in front-line therapy of acute promyelocytic leukemia (C9710): prognostic significance of FLT3 mutations and complex karyotype. Issue 7 (July 2014) - Poiré, Xavier; Moser, Barry K.; Gallagher, Robert E.; Laumann, Kristina; Bloomfield, Clara D.; Powell, Bayard L.; Koval, Gregory; Gulati, Kabir; Holowka, Nicholas; Larson, Richard A.; Tallman, Martin S.; Appelbaum, Frederick R.; et al.
Abstract The addition of arsenic trioxide (ATO) to frontline therapy of acute promyelocytic leukemia (APL) has been shown to result in significant improvements in disease-free survival (DFS). FLT3 mutations are frequently observed in APL, but its prognostic significance remains unclear. We analyzed 245 newly diagnosed adult patients with APL treated on intergroup trial C9710 and evaluated previously defined biological and prognostic factors and their relationship to FLT3 mutations and to additional karyotypic abnormalities. FLT3 mutations were found in 48% of patients, including 31% with an internal tandem duplication (FLT3-ITD), 14% with a point mutation (FLT3-D835) and 2% with both mutations. The FLT3-ITD mutant level was uniformly low, < 0.5. Neither FLT3 mutation had an impact on remission rate, induction death rate, DFS or overall survival (OS). The addition of ATO consolidation improved outcomes regardless of FLT3 mutation type or level, initial white blood cell count, PML–RARA isoform type or transcript level. The presence of a complex karyotype was strongly associated with an inferior OS independently of post-remission treatment. In conclusion, the addition of ATO to frontline therapy overcomes the impact of previously described adverse prognostic factors including FLT3 mutations. However, complex karyotype is strongly associated with an inferior OS despite ATO therapy.